Biodriven investigation of the wild edible mushroom Pleurotus eryngii revealing unique properties as functional food - Teniou, Soumia; Bensegueni, Abderrahmane; Hybertson, Brooks M.; Gao, Bifeng; Bose, Swapan K.; McCord, Joe M.; Chovelon, Benoît; Bensouici, Chawki; Boumendjel, Ahcène; Hininger-Favier, Isabelle (Journal of functional foods, 2022)
[Display omitted] •Pleurotus eryngii extract activate the Nrf2 and enhance the antioxidant activity.•N-acetyl tryptamine found in Pleurotus eryngii inhibits acetylcholinesterase.•Pleurotus eryngii contain high level of Zinc and other essential trace elements.•Pleurotus eryngii extract acts on several genes expression, suggesting potential protection against life threatening diseases. Pleurotus eryngii (P. eryngii) is largely represented among consumed mushrooms. We conducted an investigation dealing with its antioxidant potential, the presence of essential trace elements and its contribution to the management of brain-related disorders. A bio-guided extraction revealed that one extract was highly effective on activation of the nuclear factor Nrf2, the regulator of the cellular resistance to oxidants. Its analysis revealed the presence of N-acetyltryptamine (NAT), a precursor of the neurotransmitters, melatonin and serotonin. Both extract and NAT, were found as competitive inhibitors of acetylcholinesterase. The essential trace elements analyses showed the presence of high amounts of zinc. RNA-seq technology confirmed upregulates expression of Nrf2 on HepG2 cells and revealed key genes involved in anticholesterolemic, antioxidant effects, cancer and brain disorders. Our study achieved a comprehensive strengthening of the nutritional health-benefit properties of P. eryngii largely used in folk medicines and open perspectives for investigation in food and medicine.